PENDAMPINGAN PENERAPAN SISTEM INFORMASI KEUANGAN DESA (SISKEUDES) PADA BADAN USAHA MILIK DESA - Silviyani, Yuli Anita; Afandi, Agus; Amalya, Neneng Tita (Jurnal Pajak Populis, 2025)
This community service activity aims to assist the implementation of the Village Financial Information System (SISKEUDES) in Badan Usaha Milik Desa (BUMDes) Multi Prospekta, Suka Negara Village, Jonggol District, Bogor Regency. The main objective of this program is to improve financial management efficiency, transparency, and accountability through digital-based accounting systems. The methods used include needs assessment, digital accounting training, system implementation assistance, monitoring, and evaluation. The activity involved BUMDes managers as participants who were guided in recording financial transactions, preparing financial reports, and utilizing SISKEUDES features. The results show an improvement in participants’ understanding and skills in financial recording and reporting, as well as increased transparency in managing village business finances. This activity contributes to strengthening village economic governance and supports sustainable rural development through accountable financial management